Shoulder pain and dysphagia with an unexpected cause. (2nd February 2011) - Mullish, Benjamin H; Apps, Andrew; Damani, Nizar
Abstract : A 31-year-old female pharmacist of Nigerian origin, now resident in London, described 4 months of worsening left-sided subscapular pain despite the use of increasingly potent analgesia. She also described progressive dysphagia, first to solids and later to liquid foods. She remained systemically well, with no associated symptoms and normal physiological observations. In light of raised plasma inflammatory markers and chest radiography demonstrating a widened paraspinal stripe, the patient underwent CT and subsequent MRI of the thorax and upper spine. This revealed bony destruction of multiple higher thoracic vertebrae, with an associated epidural abscess mediating spinal cord impingement at T5. A large prevertebral collection spanning C7–T9 directly compressing and displacing the oesophagus was demonstrated. These findings collectively suggested spinal tuberculosis (Pott's disease); PCR confirmed the presence of Mycobacterium tuberculosis . The patient was successfully treated with oral anti-tuberculous chemotherapy and physiotherapy.